2018
DOI: 10.1039/c8cp00697k
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in two-dimensional phosphorus carbide (β0-PC)

Abstract: Two-dimensional (2D) boron has been predicted to show superconductivity. However, intrinsic 2D carbon and phosphorus have not been reported to be superconductors, which has inspired us to study the superconductivity of their mixture. Here we performed first-principles calculations for the electronic structure, phonon dispersion, and electron-phonon coupling of the metallic phosphorus carbide monolayer, β0-PC. The results show that it is an intrinsic phonon-mediated superconductor, with an estimated superconduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 71 publications
1
25
0
Order By: Relevance
“…Thermal treatments have an effect on the transduction of HCl‐doped PANI nanofibers integrated in conductometric devices upon exposure to 1% H 2 (carried by N 2 ) . After drying in N 2 at ca 25 °C for 12 h, sensors based on PANI nanofibers showed a 10% decrease in electrical resistance upon exposure to 1% H 2 .…”
Section: Applicationsmentioning
confidence: 99%
“…Thermal treatments have an effect on the transduction of HCl‐doped PANI nanofibers integrated in conductometric devices upon exposure to 1% H 2 (carried by N 2 ) . After drying in N 2 at ca 25 °C for 12 h, sensors based on PANI nanofibers showed a 10% decrease in electrical resistance upon exposure to 1% H 2 .…”
Section: Applicationsmentioning
confidence: 99%
“…Also, it has been found that black phosphorus in both orthorhombic and rhombohedral structures can intrinsically develop superconductivity [21][22][23][24][25][26][27][28][29][30][31] . However, the dominant pairing type in BP has brought up discussions and is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45 ] γ‐PC and β 0 ‐PC were proposed as alkali‐metal‐ion battery materials. [ 46,47 ] In our previous work, we have also predicted β 0 ‐PC to be an intrinsic phonon‐mediated superconductor, with an estimated superconducting temperature T normalc of ≈13 K. [ 48 ]…”
Section: Introductionmentioning
confidence: 99%